Whole exome sequencing identified a novel POT1 variant as a candidate pathogenic allele underlying a Li–Fraumeni-like family - Li, Yuping; Xie, Yupeng; Wang, Di; Xu, Hanyan; Ye, Junru; Yin, Jiani C.; Chen, Junjie; Yan, Junrong; Ye, Bin; Chen, Chengshui (Frontiers in Oncology, 2022)
Abstract Background: Li-Fraumeni syndrome (LFS) and Li-Fraumeni-like (LFL) syndrome are rare hereditary diseases characterized by predisposition to a diverse spectrum of cancer types, primarily sarcoma. The pathogenic variants underlying the majority of LFL cases remain to be explored. Methods: We performed whole-exome sequencing (WES) on 13 core members of a large LFL family with highly aggregated incidences of cancers, including cases with sarcoma, non-small cell lung cancer and cardiac angiosarcoma, and conducted a comprehensive literature review of candidate gene associations in LFS/LFL syndromes or sarcoma to identify potential pathogenic germline variants. Results: No germline variants in the best-known LFL/LFS-associated gene TP53 were detected. Of all the genes associated with LFS/LFL or sarcoma that we have surveyed, we identified a novel p.P35L germline variant in POT1 (protection of telomeres 1). Germline and somatic alterations in POT1 have been implicated in a series of familial cancers, including angiosarcoma, glioma, melanoma and colorectal cancer. This particular variant is located in the telomere-binding OB1 domain, which is important in maintaining the proper telomere length, and showed high conservation across different POT1 orthologues. No record of the variant was found in any of the 1000 genomes, ExAC, gnomAD, dpSNP and COSMIC databases. Prediction algorithms and in silico structural analysis suggested completely disrupted protein structure and function of POT1 in the presence of this mutation. Conclusions: Leveraging WES, we identified a novel germline risk allele, p.P35L in POT1, that likely predisposes to LFL syndrome. Our results support the routine testing of POT1 and other LFL/LFS-associated genes in the risk populations to enable early cancer diagnosis, prevention and intervention.